COMPLEX INVESTIGATIONS OF THE PROCESSES OF FORMING OF THE UNINTERRUPTEDLYCASTED STEEL SLUGS WITH THE PURPOSE OF REFINEMENT - V. I. Timoshpolski; Ju. A. Samojlovich; N. V. Andrianov; I. A. Trusova; S. M. Kabishov (Литьë и металлургия)
There is developed the procedure of calculation of the interrelated processes of hardening and crystallization, allowing to determine the metallurgical length of the slug and parameters of zones of the acicular (dendritic) and globular (volume) crystallization